2016
DOI: 10.2399/ana.16.044
|View full text |Cite
|
Sign up to set email alerts
|

Partial corpus callosum agenesis and colpocephaly: a case report

Abstract: Callosal abnormalities are mostly described as central nervous system malformations and can be symptomatic or asymptomatic. Herein, we report an autopsy case of a 50-year-old Syrian immigrant male with poor academic performance, presented with partial agenesis of the corpus callosum and colpocephaly. He was evidently asymptomatic until death.The cause of death was determined to be hypothermia. Autosy revealed a corpus callosum of 3 cm only in the anterior part. Posterior part of the corpus callosum, anterior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Adult patients usually present with nonspecific symptoms such as headache [1 , 2 , 3 , 10] , dizziness [2 , 6] , seizures [6 , 11] , vertigo [1] , nausea [6] , motor abnormalities [16] , sensory abnormalities [12] , cognitive abnormalities [15 , 17] , intellectual disability [18] , learning disability [17] , gait instability and falls [9] , loss of consciousness [13] and visual hallucinations [19] . Gungor et al reported a case with postmortem diagnosis of colpocephaly in a patient with a lifelong history of poor academic performance [20] . Some cases had other primary diagnoses such as meningioma [2] and paraspinal abscess as a complication of spine surgery [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients usually present with nonspecific symptoms such as headache [1 , 2 , 3 , 10] , dizziness [2 , 6] , seizures [6 , 11] , vertigo [1] , nausea [6] , motor abnormalities [16] , sensory abnormalities [12] , cognitive abnormalities [15 , 17] , intellectual disability [18] , learning disability [17] , gait instability and falls [9] , loss of consciousness [13] and visual hallucinations [19] . Gungor et al reported a case with postmortem diagnosis of colpocephaly in a patient with a lifelong history of poor academic performance [20] . Some cases had other primary diagnoses such as meningioma [2] and paraspinal abscess as a complication of spine surgery [4] .…”
Section: Discussionmentioning
confidence: 99%